Gardening and Urban Agriculture as Physical Activity Interventions for Stroke Prevention in Older Adults: A Systematic Review - Maria Aditia Wahyuningrum; Siti M. Sholihah; Luluk Syahr Banu; Suryani; Reni Nurjasmi (Science Tech Group, 2026)
Background: While physical inactivity remains a major, modifiable risk factor for stroke and long-term disability in older adults, sustaining conventional exercise routines often proves challenging. Consequently, gardening and urban agriculture are gaining traction as accessible, sustainable physical activities that actively promote healthy aging. Objective: To synthesize existing evidence, this systematic review evaluates the impact of gardening and urban agriculture as physical activity interventions for stroke prevention in aging populations. Methods: Adhering to PRISMA guidelines, we conducted comprehensive searches across the PubMed, Scopus, and Dimensions databases for literature published between 2015 and 2026. Eligibility was restricted to studies of adults aged 60 and older who engaged in horticultural therapy, community or home gardening, or urban agriculture, with reported outcomes related to cardiovascular health and active aging. Results: Out of 322 initial records, five studies qualified for full qualitative synthesis. The reviewed literature indicates that gardening interventions reliably enhance mobility, physical exertion, cardiovascular health, psychological resilience, and social interaction among older adults. By naturally mitigating sedentary behaviors and improving modifiable cardiovascular risk factors, these activities indirectly contribute to stroke prevention. Conclusion: Although methodological heterogeneity across the studies and a scarcity of controlled experimental trials preclude definitive causal conclusions, the current evidence is highly promising. Gardening and urban agriculture offer viable, cost-effective, and community-integrated strategies to advance active aging, elevate overall well-being, and reduce stroke vulnerability among older adults.